2019
DOI: 10.1111/micc.12548
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic source of protease activity in the spontaneously hypertensive rat and its reduction during temporary food restriction

Abstract: Objective: The mechanisms underlying cell and organ dysfunctions in hypertension are uncertain. The spontaneously hypertensive rat (SHR) has elevated levels of unchecked degrading proteases compared to the control Wistar Kyoto (WKY) rat. The extracellular proteases destroy membrane receptors leading to cell dysfunctions, including arteriolar constriction and elevated blood pressure. Our goal was to identify potential sources of the uncontrolled enzymatic activity. Methods: Zymographic and digital immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In addition, acidic amino acids (Asp and Glu) can chelate zinc atoms, which are cofactors of ACE [31]. This study confirms the hypotensive and anti-hypertensive effects of the Bowman-Birk protease inhibitor, particularly inhibiting trypsin and chymotrypsin [32]. This property contributes to the bioavailability of peptides with ACE inhibitory activity [33].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, acidic amino acids (Asp and Glu) can chelate zinc atoms, which are cofactors of ACE [31]. This study confirms the hypotensive and anti-hypertensive effects of the Bowman-Birk protease inhibitor, particularly inhibiting trypsin and chymotrypsin [32]. This property contributes to the bioavailability of peptides with ACE inhibitory activity [33].…”
Section: Discussionsupporting
confidence: 71%
“…Oxidative stress, a phenomenon of the imbalance of oxidation and antioxidation, would result from a variety of diseases or environmental stimuli, such as hypertension. , ROS is the most important marker of oxidative damage which could be activated by ET-1 . Excessive ROS attacks polyunsaturated fatty acids in the cell membrane through lipid peroxidation to generate MDA, which is regarded a common biomarker for in vivo oxidative stress and a bioactive trigger for inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that uncontrolled proteolytic receptor cleavage occurs in microcirculation in hypertension patients, leading to cellular and systemic dysfunction and even end-organic damage. 8–10 It has been proven that the pancreas serves as a major systemic major source of digestive enzymes (mainly serine proteases, 11 such as matrix metalloproteinases 12 , 13 and trypsin 14 ) in the microcirculation and surrounding tissues, 15 which may be one of the explanations underlying enhanced protease activity in SHRs 16 and the generated pathophysiological response of clinical manifestations observed in hypertensive individuals. These lines of evidence highlight the importance of pancreatic microcirculation in the development of hypertension.…”
mentioning
confidence: 99%